The Science of Science Communication II: Summary of a Colloquium (The National Academies Press, 2014)
Successful scientists must be effective communicators within their professions. Without those skills, they could not write papers and funding proposals, give talks and field questions, or teach classes and mentor students. However, communicating with audiences outside their profession - people who may not share scientists' interests, technical background, cultural assumptions, and modes of expression - presents different challenges and requires additional skills. Communication about science in political or social settings differs from discourse within a scientific discipline. Not only are scientists just one of many stakeholders vying for access to the public agenda, but the political debates surrounding science and its applications may sometimes confront scientists with unfamiliar and uncomfortable discussions involving religious values, partisan interests, and even the trustworthiness of science. The Science of Science Communication II is the summary of a Sackler Colloquium convened in September 2013 At this event, leading social, behavioral, and decision scientists, other scientists, and communication practitioners shared current research that can improve the communication of science to lay audiences. In the Sackler Colloquia tradition, the meeting also allowed social and natural scientists to identify new opportunities to collaborate and advance their own research, while improving public engagement with science. Speakers provided evidence-based guidance on how to listen to others so as to identify their information needs, ways of thinking about the world, and the cultural stereotypes regarding scientists. They delved deeply into the incentive systems that shape what scientists study and how they report their work, the subtle changes in framing that can influence how messages are interpreted, the complex channels that determine how messages flow, and the potential politicization of scientific evidence.
Keywords: Policy for Science and Technology

Communicating Science Effectively: A Research Agenda - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
Science and technology are embedded in virtually every aspect of modern life. As a result, people face an increasing need to integrate information from science with their personal values and other considerations as they make important life decisions about medical care, the safety of foods, what to do about climate change, and many other issues. Communicating science effectively, however, is a complex task and an acquired skill. Moreover, the approaches to communicating science that will be most effective for specific audiences and circumstances are not obvious. Fortunately, there is an expanding science base from diverse disciplines that can support science communicators in making these determinations. Communicating Science Effectively offers a research agenda for science communicators and researchers seeking to apply this research and fill gaps in knowledge about how to communicate effectively about science, focusing in particular on issues that are contentious in the public sphere. To inform this research agenda, this publication identifies important influences – psychological, economic, political, social, cultural, and media-related – on how science related to such issues is understood, perceived, and used.
Keywords: Policy for Science and Technology

Science Literacy: Concepts, Contexts, and Consequences - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
Science is a way of knowing about the world. At once a process, a product, and an institution, science enables people to both engage in the construction of new knowledge as well as use information to achieve desired ends. Access to science—whether using knowledge or creating it—necessitates some level of familiarity with the enterprise and practice of science: we refer to this as science literacy. Science literacy is desirable not only for individuals, but also for the health and well- being of communities and society. More than just basic knowledge of science facts, contemporary definitions of science literacy have expanded to include understandings of scientific processes and practices, familiarity with how science and scientists work, a capacity to weigh and evaluate the products of science, and an ability to engage in civic decisions about the value of science. Although science literacy has traditionally been seen as the responsibility of individuals, individuals are nested within communities that are nested within societies—and, as a result, individual science literacy is limited or enhanced by the circumstances of that nesting. Science Literacy studies the role of science literacy in public support of science. This report synthesizes the available research literature on science literacy, makes recommendations on the need to improve the understanding of science and scientific research in the United States, and considers the relationship between scientific literacy and support for and use of science and research.
Keywords: Education

The Science of Science Communication III: Inspiring Novel Collaborations and Building Capacity: Proceedings of a Colloquium - National Academy of Sciences (The National Academies Press, 2018)
Successful scientists must be effective communicators within their professions. Without those skills, they could not write papers and funding proposals, give talks and field questions, or teach classes and mentor students. However, communicating with audiences outside their profession - people who may not share scientists' interests, technical background, cultural assumptions, and modes of expression - presents different challenges and requires additional skills. Communication about science in political or social settings differs from discourse within a scientific discipline. Not only are scientists just one of many stakeholders vying for access to the public agenda, but the political debates surrounding science and its applications may sometimes confront scientists with unfamiliar and uncomfortable discussions involving religious values, partisan interests, and even the trustworthiness of science. The Science of Science Communication III: Inspiring Novel Collaborations and Building Capacity summarizes the presentations and discussions from a Sackler Colloquium convened in November 2017. This event used Communicating Science Effectively as a framework for examining how one might apply its lessons to research and practice. It considered opportunities for creating and applying the science along with the barriers to doing so, such as the incentive systems in academic institutions and the perils of communicating science in polarized environments. Special attention was given to the organization and infrastructure necessary for building capacity in science communication.
Keywords: Policy for Science and Technology

Learning Through Citizen Science: Enhancing Opportunities by Design - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2018)
In the last twenty years, citizen science has blossomed as a way to engage a broad range of individuals in doing science. Citizen science projects focus on, but are not limited to, nonscientists participating in the processes of scientific research, with the intended goal of advancing and using scientific knowledge. A rich range of projects extend this focus in myriad directions, and the boundaries of citizen science as a field are not clearly delineated. Citizen science involves a growing community of professional practitioners, participants, and stakeholders, and a thriving collection of projects. While citizen science is often recognized for its potential to engage the public in science, it is also uniquely positioned to support and extend participants' learning in science. Contemporary understandings of science learning continue to advance. Indeed, modern theories of learning recognize that science learning is complex and multifaceted. Learning is affected by factors that are individual, social, cultural, and institutional, and learning occurs in virtually any context and at every age. Current understandings of science learning also suggest that science learning extends well beyond content knowledge in a domain to include understanding of the nature and methods of science. Learning Through Citizen Science: Enhancing Opportunities by Design discusses the potential of citizen science to support science learning and identifies promising practices and programs that exemplify the promising practices. This report also lays out a research agenda that can fill gaps in the current understanding of how citizen science can support science learning and enhance science education.
Keywords: Education

Sustainable Infrastructures for Life Science Communication: Workshop Summary - National Research Council (The National Academies Press, 2014)
Advances in the life sciences - from the human genome to biotechnology to personalized medicine and sustainable communities - have profound implications for the well-being of society and the natural world. Improved public understanding of such scientific advances has the potential to benefit both individuals and society through enhanced quality of life and environmental protection, improved K-12 and undergraduate science education, greater understanding of human connections to the natural world, and more sustainable policies and regulations. Yet few systems of support exist to help life scientist communicators share their research with a broad range of public audiences, or engage the public in discussions about their work. Sustainable Infrastructures for Life Science Communication is the summary of a two-part workshop convened in December 2013 and January 2014 by the National Research Council Roundtable on Public Interfaces of the Life Sciences to identify infrastructure-related barriers that inhibit or prohibit life scientists from communicating about their work and characteristics of infrastructure that facilitate or encourage scientists to engage with public audiences. The workshop featured both formal presentations and panel discussions among participants from academia, industry, journalism, the federal government, and nonprofit organizations. The presentations highlighted the motivations of and challenges to life scientist communicators, theoretical approaches to science communication, examples of different types of infrastructure to support science communication, and the need for building more sustainable science communication infrastructures. This report considers communication infrastructure across a range of life science institutions, including federal agencies, academia, industry, and nonprofit organizations and explores novel approaches to facilitate effective science communication.
Keywords: Biology and Life Sciences; Education

Communicating Chemistry: A Framework for Sharing Science: A Practical Evidence-Based Guide - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
A growing body of evidence indicates that, increasingly, the public is engaging with science in a wide range of informal environments, which can be any setting outside of school such as community-based programs, festivals, libraries, or home. Yet undergraduate and graduate schools often don’t prepare scientists for public communication. This practical guide is intended for any chemist – that is, any professional who works in chemistry-related activities, whether research, manufacturing or policy – who wishes to improve their informal communications with the public. At the heart of this guide is a framework, which was presented in the report Effective Chemistry Communication in Informal Environments and is based on the best available empirical evidence from the research literature on informal learning, science communication, and chemistry education. The framework consists of five elements which can be applied broadly to any science communication event in an informal setting.
Keywords: Math, Chemistry, and Physics; Education

Public Engagement on Genetically Modified Organisms: When Science and Citizens Connect: Workshop Summary - National Research Council (The National Academies Press, 2015)
The National Research Council's Roundtable on Public Interfaces of the Life Sciences held a 2-day workshop on January 15-16, 2015, in Washington, DC to explore the public interfaces between scientists and citizens in the context of genetically engineered (GE) organisms. The workshop presentations and discussions dealt with perspectives on scientific engagement in a world where science is interpreted through a variety of lenses, including cultural values and political dispositions, and with strategies based on evidence in social science to improve public conversation about controversial topics in science. The workshop focused on public perceptions and debates about genetically engineered plants and animals, commonly known as genetically modified organisms (GMOs), because the development and application of GMOs are heavily debated among some stakeholders, including scientists. For some applications of GMOs, the societal debate is so contentious that it can be difficult for members of the public, including policy-makers, to make decisions. Thus, although the workshop focused on issues related to public interfaces with the life science that apply to many science policy debates, the discussions are particularly relevant for anyone involved with the GMO debate. Public Engagement on Genetically Modified Organisms: When Science and Citizens Connect summarizes the presentations and discussion of the workshop.
Keywords: Agriculture; Education; Biology and Life Sciences

Trust and Confidence at the Interfaces of the Life Sciences and Society: Does the Public Trust Science? A Workshop Summary - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2015)
Does the public trust science? Scientists? Scientific organizations? What roles do trust and the lack of trust play in public debates about how science can be used to address such societal concerns as childhood vaccination, cancer screening, and a warming planet? What could happen if social trust in science or scientists faded? These types of questions led the Roundtable on Public Interfaces of the Life Sciences of the National Academies of Sciences, Engineering, and Medicine to convene a 2-day workshop on May 5-6, 2015 on public trust in science. This report explores empirical evidence on public opinion and attitudes toward life sciences as they relate to societal issues, whether and how contentious debate about select life science topics mediates trust, and the roles that scientists, business, media, community groups, and other stakeholders play in creating and maintaining public confidence in life sciences. Does the Public Trust Science? Trust and Confidence at the Interfaces of the Life Sciences and Society highlights research on the elements of trust and how to build, mend, or maintain trust; and examine best practices in the context of scientist engagement with lay audiences around social issues.
Keywords: Biology and Life Sciences; Education; Behavioral and Social Sciences

Effective Health Communication Within the Current Information Environment and the Role of the Federal Government: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
On March 20 and 21, 2023, the Board on Science Education at the National Academies of Sciences, Engineering, and Medicine hosted a workshop titled Effective Health Communication within the Current Information Environment and the Role of the Federal Government. Workshop speakers and participants, a majority of whom were working in government agencies in federal health communication or leadership positions, joined both in person in Washington, D.C. as well as virtually to explore the current health information environment as it pertains to public trust and behavior change, explore how federal health agencies can communicate effectively within the current information environment and what is needed to support effective health communication moving forward. This publication summarizes the presentations and discussion of the workshop.
Keywords: Education

Effective Chemistry Communication in Informal Environments - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
Chemistry plays a critical role in daily life, impacting areas such as medicine and health, consumer products, energy production, the ecosystem, and many other areas. Communicating about chemistry in informal environments has the potential to raise public interest and understanding of chemistry around the world. However, the chemistry community lacks a cohesive, evidence-based guide for designing effective communication activities. This report is organized into two sections. Part A: The Evidence Base for Enhanced Communication summarizes evidence from communications, informal learning, and chemistry education on effective practices to communicate with and engage publics outside of the classroom; presents a framework for the design of chemistry communication activities; and identifies key areas for future research. Part B: Communicating Chemistry: A Framework for Sharing Science is a practical guide intended for any chemists to use in the design, implementation, and evaluation of their public communication efforts.
Keywords: Math, Chemistry, and Physics; Education

Changing the Conversation: Messages for Improving Public Understanding of Engineering - National Academy of Engineering (The National Academies Press, 2008)
Can the United States continue to lead the world in innovation? The answer may hinge in part on how well the public understands engineering, a key component of the 'innovation engine'. A related concern is how to encourage young people--particularly girls and under-represented minorities--to consider engineering as a career option. Changing the Conversation provides actionable strategies and market-tested messages for presenting a richer, more positive image of engineering. This book presents and discusses in detail market research about what the public finds most appealing about engineering--as well as what turns the public off. Changing the Conversation is a vital tool for improving the public image of engineering and outreach efforts related to engineering. It will be used by engineers in professional and academic settings including informal learning environments (such as museums and science centers), engineering schools, national engineering societies, technology-based corporations that support education and other outreach to schools and communities, and federal and state agencies and labs that do or promote engineering, technology, and science.
Keywords: Education; Engineering and Technology

Messaging for Engineering: From Research to Action - National Academy of Engineering (The National Academies Press, 2013)
For those in the broad engineering community--those who employ, work with, and/or educate engineers, and engineers themselves--there is no need to explain the importance and value of engineering. They understand that engineers help make the world a better place for all, that they regularly grapple with important societal and environmental issues, and that the engineering process is every bit as creative as composing a symphony or crafting a piece of art. But the situation outside the engineering community is quite different. Studies have shown that most K-12 students and teachers have a limited appreciation of all the ways that engineering makes their lives better and, furthermore, that they have little understanding of what engineers do or of the opportunities that an engineering education offers. Messaging for Engineering supports efforts by the engineering community to communicate more effectively about the profession and those who practice it. This report builds on the 2008 NAE publication, Changing the Conversation: Messages for Improving Public Understanding of Engineering (CTC), which presented the results of a research-based effort to develop and test new, more effective messages about engineering. The new messages cast engineering as inherently creative and concerned with human welfare, as well as an emotionally satisfying calling. This report summarizes progress in implementing the CTC messages, but also recognizes that there is potential to galvanize additional action and thus suggests specific steps for major players in the engineering community to continue and build on progress to date. Many of the report's recommendations resulted from discussion at a December 2010 committee workshop that involved several dozen high-level decision makers representing key stakeholder groups in the engineering community.
Keywords: Engineering and Technology